E-Band Beam-Steerable and Scalable Phased Antenna Array for 5G Access Point - Md. Mazidul Islam; Mikko Leino; Rasmus Luomaniemi; Jinsong Song; Risto Valkonen; Juha Ala-Laurinaho; Ville Viikari (International Journal of Antennas and Propagation)
This paper presents a new implementation of the beam-steerable two-dimensional phased antenna array for the forthcoming 5G networks. The antenna enables easy integration of phase shifters and other active electronics on a single PCB, low-loss feed network, low profile, and beam steering in both azimuth and elevation plane. In addition, the antenna is scalable in the number of elements and it can be made compatible with low-cost mass production in plastic injection molding with a metal coating. The antenna consists of a rectangular waveguide feed network, waveguide-to-PCB transitions, phase shifters on a PCB, and horn antenna radiating elements. The parts have been first designed and simulated individually and the operation of the whole structure is then verified by electromagnetic simulations. The phase shifter used in this work is a meandered microstrip line section, but the structure also enables the implementation of active phase shifters. A four-by-four antenna array prototype was manufactured. The beam-steering properties of the phased antenna array have been tested with radiation pattern measurements at 72.5 GHz, and the measured gains are compared with the simulated ones. The measured gains are 15.2 and 11.2 dBi for the boresight beam, and the beam was steered to 40°.